'Making Room for the Other(s)': A consideration of psychodynamic counselling with women with Asperger's Syndrome. Issue 2 (3rd April 2018) - Gould, Rachel
Abstract : This paper explores psychodynamic therapy with young women with Aspergers Syndrome through the use of a composite case study. It seeks to make sense of a female patient's obsession with a figure from celebrity culture – 'Tom' from 'Britain's Got Talent'. The potential use of 'Tom' by the patient as an idealised object, an autistic object, a transitional object and a transformative object is considered. Drawing on Rosenfeld's concept of pathological narcissism and Meltzer's concept of 'aesthetic reciprocity', the paper seeks to make sense of both the defences that the patient utilises and the impact of the deficits she has experienced. Attention is given to the development of the therapy through the use of play and work in the transference. Gradually, the patient becomes more able to tolerate separateness and in doing so becomes more connected to her own internal world and the feelings of others. In so doing, she becomes more aware of her actual social marginalisation and gains a greater sense of awareness of her diagnosis.